The value of cervical length to predict preterm birth. - Saleh, Hasan; Selman, Safaa; Said, Nawar (Latakia University Journal -Medical Sciences Series, 2018)
Purpose: To study the value of cervical length measured by vaginal ultrasound in 2nd or 3rd trimester of pregnancy in predicting preterm birth. Setting: Tishreen University Hospital, Lattakia, Syria. Methods: We measured the cervical length of 308 pregnant "pregnancy age between 24-34 weeks" by vaginal ultrasound. We followed them till birth. Results: In the study sample the preterm birth rate was 10.08%. The rate of preterm birth declined as the cervical length increased (preterm birth rate was 55.56% for cervical length between 20-24 mm and 9.43% for cervical length between 30-34 mm). The rate of preterm birth was lower for the longer cutoff value. The sensitivity of cutoff value "25 mm" was poor, but with good specificity (16.13%, 98.56% respectively). Conclusion: The cervical length is a good predictor for preterm birth. The cutoff value (≤25 mm) has good specificity and negative predictive value. دور طول عنق الرحم بالتنبؤ بالولادات الباكرة هدف الدراسة: دراسة قيمة طول عنق الرحم من خلال التصوير بالامواج فوق الصوتية عبر المهبل في الثلث الثاني والثالث الحملي للتنبؤ بالولادة الباكرة. المكان: مشفى تشرين الجامعي، اللاذقية، سوريا. الطرائق: تمت قياس طول عنق الرحم بالإيكو المهبلي لدى 308 حوامل "كان العمر الحملي بين 24-34 أسبوع"، وتمت متابعتهن حتى الولادة. النتائج: كان معدل الولادة الباكرة في عينة الدراسة 10.08%. كان هناك انخفاض في النسبة المئوية لحدوث الولادة الباكرة كلما كان طول عنق الرحم أكبر (بلغت نسبة الولادة الباكرة 55.56% في حالة عنق رحم بين 20-24ملم، بينما بلغت 9.43% بالنسبة لطول عنق رحم 30-34ملم)، كما كانت النسبة أخفض كلما كانت القيمة الحدية المدروسة أكبر. كانت الحساسية للقيمة الحدية 25 ملم سيئة، ولكن مع نوعية جيدة (16.13%، 98.56% على الترتيب). الخلاصة: قياس طول عنق الرحم منبئ جيد للولادة الباكرة، إن القيمة الحدية (≤25 ملم) تملك نوعية وقيمة تنبؤية سلبية جيدة.